Observing versus creating flowers: a review of relevance for art therapy - Huss, Ephrat; Nagamine, Mitsue; Zaccai, Michele (Frontiers in Human Neuroscience, 2025)
This paper compares the embodied aesthetic experience of three types of images: photographed flowers, drawn flowers, and mandalas, summarizing data from three former comparative papers. The findings denote the strong embodied emotional connection of participants (changes in mood expressed in neural and physiological responses) to images of real flowers, as compared to the more cognitive reactions to drawings of flowers and cognitive stimulation of flower-like mandalas. These findings are discussed in terms of methodological relevance for art therapy and nature therapy. While it is known that flowers arouse positive emotions, this more nuanced comparison has interesting implications for visual art therapy, and for the therapeutic effects of nature photos, as opposed to drawn interpretations of nature.